An algebraic treatment of the Askey biorthogonal polynomials on the unit circle. (7th October 2021) - Vinet, Luc; Zhedanov, Alexei
Abstract: A joint algebraic interpretation of the biorthogonal Askey polynomials on the unit circle and of the orthogonal Jacobi polynomials is offered. It ties their bispectral properties to an algebra called the meta-Jacobi algebra $m\mathfrak {J}$ .